Nekaj hipotez o kvadraturi kroga: ustava SFRJ in proces osamosvajanja Republike Slovenije - Žagar, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1994)
This article analyzes the role of the Constitution of the Socialist Federative Republic of Yugoslavia of 1974 in the process of dismantling of the former Yugoslav federation and in creating of the independent Republic of Slovenia. Special attention is paid to ethnic dimensions of the federation in these processes. The role of the Constitution of the SFRY was controversial. Though, the main problem of the Constitution of the SFRY of 1974 was that it did not provide mechanisms and procedures for the detection, management and resolution of (possible)ethnic and other social conflicts.
Keywords: 1974; federalizem; Jugoslavija; narodnostno vprašanje; osamosvojitev; Slovenija; ustave; večnacionalne države